2011
DOI: 10.1523/jneurosci.2358-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Profiling of Spiral Ganglion Neurons Reveals Insights into Auditory Circuit Assembly

Abstract: The sense of hearing depends on the faithful transmission of sound information from the ear to the brain by spiral ganglion (SG) neurons. However, how SG neurons develop the connections and properties that underlie auditory processing is largely unknown. We catalogued gene expression in mouse SG neurons from embryonic day 12 (E12), when SG neurons first extend projections, up until postnatal day 15 (P15), after the onset of hearing. For comparison, we also analyzed the closely-related vestibular ganglion (VG).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
145
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(164 citation statements)
references
References 69 publications
18
145
1
Order By: Relevance
“…DiI tracing experiments on the trigeminal ganglion in the absence of CNP, Npr2, or cGKI further support the notion that these three cGMP signaling components that were identified to be important for axonal branching in DRG neurons also control branching of cranial sensory neurons. In addition, a recently published study on DiI tracing of the VIII th nerve in Npr2 cn/cn mice also supports our overall conclusions (Lu et al, 2011). In contrast, collateral formation is not impaired in the absence of Npr2-induced cGMP signaling, which is consistent with our view that distinct signaling cascades already exist in a single neuron to regulate distinct branching modes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…DiI tracing experiments on the trigeminal ganglion in the absence of CNP, Npr2, or cGKI further support the notion that these three cGMP signaling components that were identified to be important for axonal branching in DRG neurons also control branching of cranial sensory neurons. In addition, a recently published study on DiI tracing of the VIII th nerve in Npr2 cn/cn mice also supports our overall conclusions (Lu et al, 2011). In contrast, collateral formation is not impaired in the absence of Npr2-induced cGMP signaling, which is consistent with our view that distinct signaling cascades already exist in a single neuron to regulate distinct branching modes.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, at more advanced developmental stages, several other neuronal subpopulations in the brain are found to be positive for Npr2 and cGKI␣, including subpopulations in the cerebellum, hippocampus, and thalamus. However, the second messenger cGMP is implicated in several developmental and physiological processes in which cGMP signaling components are organized and function in different combinations (Lucas et al, 2000;Hofmann et al, 2006). A careful histological analysis of the localization of cGMP signaling components is therefore required before axonal branching studies are performed on these neuronal subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of select genes was validated by summarizing their reported expression in the mouse cochlear hair cells based on RNASeq (12) or mouse spiral ganglion neurons based on GeneChips (13). Both databases catalog changes in gene expression during embryonic and early postnatal development.…”
Section: Methodsmentioning
confidence: 99%
“…Although the molecular pathways that underlie the specification of cochlear vs. vestibular neurons are poorly understood, it has been reported that Gata3, the earliest known indicator of cell fate for cochlear ganglion neurons, is expressed in the developing cochlear ganglion, but not in the vestibular ganglion, as early as E13.5 (Lawoko-Kerali et al, 2004). Another study showed that the cochlear and vestibular ganglia in the CVG are molecularly distinct, as they express different combinations of cell surface receptors as early as E12.0 (Lu et al, 2011). However, an earlier study of the mouse ear at E12.5 showed that the medial and lateral populations of aggregating neuroblasts that are the precursors of the cochlear and vestibular ganglia do not separate morphologically until about E14.5 (Sher, 1971).…”
Section: Olig2 and The Development Of Primary Sensory Neurons In The Earmentioning
confidence: 99%